Osteopontin Bridging Innate and Adaptive Immunity in Autoimmune Diseases. (20th December 2016) - Clemente, Nausicaa; Raineri, Davide; Cappellano, Giuseppe; Boggio, Elena; Favero, Francesco; Soluri, Maria Felicia; Dianzani, Chiara; Comi, Cristoforo; Dianzani, Umberto; Chiocchetti, Annalisa
Abstract : Osteopontin (OPN) regulates the immune response at multiple levels. Physiologically, it regulates the host response to infections by driving T helper (Th) polarization and acting on both innate and adaptive immunity; pathologically, it contributes to the development of immune-mediated and inflammatory diseases. In some cases, the mechanisms of these effects have been described, but many aspects of the OPN function remain elusive. This is in part ascribable to the fact that OPN is a complex molecule with several posttranslational modifications and it may act as either an immobilized protein of the extracellular matrix or a soluble cytokine or an intracytoplasmic molecule by binding to a wide variety of molecules including crystals of calcium phosphate, several cell surface receptors, and intracytoplasmic molecules. This review describes the OPN structure, isoforms, and functions and its role in regulating the crosstalk between innate and adaptive immunity in autoimmune diseases.